Effect of Reinforcement of Nano Al2O3 on Mechanical Properties of Al2024 NMMCs. (2015) - Raju, P. Rama Murty; Rajesh, S.; Raju, K. Sita Rama; Raju, V. Ramachandra
Abstract: For advanced aerospace applications aluminum nano metal matrix composites (NMMC's) are increasingly becoming more attractive because their properties can be enhanced through the addition of selected reinforcements. Due to their good specific strength and specific stiffness at room or elevated temperatures particulate reinforced NMMC's have recently found special interest. It is well known that the elastic properties of nano metal matrix composites are strongly influenced by micro structural parameters of the reinforcement such as shape, size, orientation, distribution and volume fraction. The main objective of this paper is to carry out a study of effect of nano Al2 O3 reinforcement on the mechanical properties of aluminum metal matrix particulate composite. The reinforcing particulates in the MMC's vary from 0% to 2% by weight with an increment of 0.5%. The liquid metallurgy method coupled with powder metallurgy is employed to fabricate the composites, in which the reinforcements are poured into the vortex created by stirring the molten metal by means of mechanical two stage stirrer. The composites so produced are subjected to tensile and hardness tests. It was observed that increasing the reinforcement content within the aluminum matrix results in significant increases in the ultimate Tensile Strength (UTS) and hardness values. Scanning Electron Micrograph (SEM) images of the cast NMMC's are also taken in order to study the dispersion of reinforcements in the matrix.